The policy focused on the HPV vaccination program against Human Papilloma Virus in Mexico: ethics aspects - Torres-Poveda, Kirvis Janneth; Cuadra-Hernández, Silvia Magali; Castro-Romero, Julieta Ivone; Madrid-Marina, Vicente (Acta Bioethica, 2011)
This article raises an ethical analysis of issues related to the introduction of new vaccines against Human Papillomavirus in Mexico, whose distribution policy attend to equity more than equality, and has as fundamental axes to cover the most vulnerable people and the lowest cost possible, i.e. serving the principles of distributive justice. The initial scheme of vaccination against this virus in Mexico has been focused on the most marginalized female population, which focuses on indigenous women. Distribution strategies for new vaccines must take into account the specific characteristics that develop these groups and analyze the ethical implications that such measures will involve; without this public health policy could increase health inequalities.